Simone Weil for the Twenty-First Century - Springsted, Eric O. (University of Notre Dame Press, 2021)
"This in-depth study examines the social, religious, and philosophical thought of Simone Weil. Simone Weil for the Twenty-First Century presents a comprehensive analysis of Weil's interdisciplinary thought, focusing especially on the depth of its challenge to contemporary philosophical and religious studies. In a world where little is seen to have real meaning, Eric O. Springsted presents a critique of the unfocused nature of postmodern philosophy and argues that Weil's thought is more significant than ever in showing how the world in which we live is, in fact, a world of mysteries. Springsted brings into focus the challenges of Weil's original (and sometimes surprising) starting points, such as an Augustinian priority of goodness and love over being and intellect, and the importance of the Crucifixion. Springsted demonstrates how the mystical and spiritual aspects of Weil's writings influence her social thought. For Weil, social and political questions cannot be separated from the supernatural. For her, rather, the world has a sacramental quality, such that life in the world is always a matter of life in God--and life in God, necessarily a way of life in the world. Simone Weil for the Twenty-First Century is not simply a guide or introduction to Simone Weil. Rather, it is above all an argument for the importance of Weil's thought in the contemporary world, showing how she helps us to understand the nature of our belonging to God (sometimes in very strange and unexpected ways), the importance of attention and love as the root of both the love of God and neighbor, the importance of being rooted in culture (and culture's service to the soul in rooting it in the universe), and the need for human beings to understand themselves as communal beings, not as isolated thinkers or willers. It will be essential reading for scholars of Weil, and will also be of interest to philosophers and theologians."--Publisher description